Brain Tumor Microvesicles: Insights into Intercellular Communication in the Nervous System - van der Vos, Kristan E. (2011)
Brain tumors are heterogeneous tumors composed of differentiated tumor cells that resemble various neural cells and a small number of multipotent cancer stem cells. These tumors modify normal cells in their environment to promote tumor growth, invasion and metastases by various ways. Recent publications show that glioblastoma cells release microvesicles that contain a select subset of cellular proteins and RNAs. These microvesicles are avidly taken up by normal cells in cell culture and can change the translational profile of these cells through delivery of tumor-derived mRNAs, which are translated into functional proteins. In addition to mRNA and proteins, microvesicles have been shown to contain microRNAs, non-coding RNAs and DNA. This commentary explores the recent advances in this novel intercellular communication route and discusses the potential physiological role of microvesicles in brain tumorigenesis.